2019
DOI: 10.5194/gmd-2018-309
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The DeepMIP contribution to PMIP4: methodologies for selection, compilation and analysis of latest Paleocene and early Eocene climate proxy data, incorporating version 0.1 of the DeepMIP database

Abstract: Abstract. The early Eocene (56 to 48 million years ago) is inferred to have been the most recent time that Earth's atmospheric CO2 concentrations exceeded 1000 ppm. Global mean temperatures were also substantially warmer than present day. As such, study of early Eocene climate provides insight into how a super-warm Earth system behaves and offers an opportunity to evaluate climate models under conditions of high greenhouse gas forcing. The Deep Time Model Intercomparison Project (DeepMIP) is a systematic model… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
82
2

Year Published

2019
2019
2020
2020

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 37 publications
(91 citation statements)
references
References 387 publications
(723 reference statements)
7
82
2
Order By: Relevance
“…Branched GDGT-derived MAAT estimates from the lower laminated lignite pre-PETM Figure 4a; Table 1), in agreement with existing proxy-based CO2 estimates for the PETM (Hollis et al, 2019). They also agree with climate model simulations which have modified specific model parameters (e.g.…”
Section: Biomarker-derived Temperature Estimates Across the Onset Of supporting
confidence: 83%
See 1 more Smart Citation
“…Branched GDGT-derived MAAT estimates from the lower laminated lignite pre-PETM Figure 4a; Table 1), in agreement with existing proxy-based CO2 estimates for the PETM (Hollis et al, 2019). They also agree with climate model simulations which have modified specific model parameters (e.g.…”
Section: Biomarker-derived Temperature Estimates Across the Onset Of supporting
confidence: 83%
“…The marine realm also indicates increasing temperatures in northern Europe during the PETM, with evidence for 3 to 4°C of surface ocean warming in both the Bay of Biscay (Bornemann et al, 2014) and the North Sea (Schoon et al, 2015). Decreasing terrestrial temperatures also differ from the global response during the PETM (Hollis et al, 2019;Jones et al, 2013;McInerney and Wing, 2011). Collectively, this implies that the biomarker-based paleotemperature proxies in the upper laminated lignite and blocky lignite are impacted by non-thermal influences or ecological signals; below we explore what these controls may be.…”
Section: Biomarker-derived Temperature Estimates Across the Onset Of mentioning
confidence: 95%
“…The Taranaki basement map is modified from Tulloch & Mortimer (2017) and palaeogeography maps modified from Strogen (2011). The Palaeogene palaeoclimate estimate is based on TEX 86 H records for New Zealand (red dashed line being the 3-point moving average), which is a proxy for sea surface temperature, from Hollis et al (2019).…”
Section: G Basement-sandstone Correlationmentioning
confidence: 99%
“…For ⌦, we test two assumptions: 1) that the foraminifera are essentially pristine, unaltered by seafloor dissolution (⌦ = 5), and 2) that the foraminifera have experienced dissolution on par with what we would expect at the site locations today. For this latter assumption, we draw ⌦ from GLODAPv2 using the paleolatitude and paleolongitude (calculated from Baatsen et al (2016), as suggested in C. Hollis et al (2019)) and the inferred Eocene water depth as described in the original publication. We use an uninformative prior standard deviation of 10 C. (Wara et al, 2005).…”
Section: Applicationsmentioning
confidence: 99%
“…J. Hollis et al, 2009C. J. Hollis et al, , 2012Bijl et al, 2013;Inglis et al, 2015;Cramwinckel et al, 2018) calibrated with BAYSPAR (Tierney & Tingley, 2014;C. Hollis et al, 2019) (Fig.…”
Section: Applicationsmentioning
confidence: 99%